2023
DOI: 10.1186/s40104-022-00825-w
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 regulation: a target to alleviate β-hydroxybutyric acid-induced mitochondrial dysfunction in bovine granulosa cells

Abstract: Background During the transition period, the insufficient dry matter intake and a sharply increased in energy consumption to produce large quantities of milk, high yielding cows would enter a negative energy balance (NEB) that causes an increase in ketone bodies (KBs) and decrease in reproduction efficiency. The excess concentrations of circulating KBs, represented by β-hydroxybutyric acid (BHBA), could lead to oxidative damage, which potentially cause injury to follicular granulosa cells (fGCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The total SOD activity and Mn SOD activity were evaluated by SOD assay kit and Mn-SOD Assay Kit with WST-8 (Beyotime Institute of Biotechnology, Shanghai, China) according to the manufacturer’s instructions, respectively [ 23 ]. The absorbance was assessed at 450 nm using a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…The total SOD activity and Mn SOD activity were evaluated by SOD assay kit and Mn-SOD Assay Kit with WST-8 (Beyotime Institute of Biotechnology, Shanghai, China) according to the manufacturer’s instructions, respectively [ 23 ]. The absorbance was assessed at 450 nm using a microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have proposed that the loss of function of SIRT3 causes significant mitochondrial dysfunction and oxidative stress [ 17 19 ]. Contrarily, the gain of function of SIRT3 can limit high levels of mitochondrial damage and oxidative stress, which in turn prevents apoptosis [ 20 , 21 ]. Recent studies have demonstrated that the down-regulation of SIRT3 leads to the development of several diseases, such as neurodegenerative diseases, cancers, and heart disease [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%